Pulmonary lesions induced by Pasteurella haemolytica in neutrophil sufficient and neutrophil deficient calves. - Breider, M A (1988)
The role of neutrophils in the development of peracute lung lesions of bovine pneumonic pasteurellosis was investigated. Eight calves were divided into two groups of four calves each. Group I was treated with intravenous phosphate-buffered saline and served as the neutrophil sufficient calves. Group II was treated with intravenous hydroxyurea which produced a state of neutropenia. When peripheral blood neutrophil numbers dropped below 300 cells/microL in group II, all calves were challenged with an intrabronchial bolus of Pasteurella haemolytica in the log phase of growth. An acute inflammatory process occurred in both groups of calves indicated by a rise in body temperature. While pulmonary lesions occurred in both groups by six hours postinoculation, they varied in pathological characteristics. Pulmonary lesions in the neutrophil sufficient calves consisted of fibrinopurulent alveolitis-bronchiolitis with associated alveolar septal necrosis, interlobular edema, and intravascular thrombi. The neutrophil deficient calves had extensive intra-alveolar edema, interlobular edema, intraalveolar hemorrhage, atelectasis, and focal areas of alveolar septal necrosis. These results show that P. haemolytica can induce severe pulmonary tissue damage through both neutrophil dependent and neutrophil independent mechanisms.